Chromosome Characterization of Festival Strawberry (Fragaria x ananassa D. var. Festival) Result of Polyploidization - Aristya, Ganies Riza; Alyza, Rezika (Biogenesis: Jurnal Ilmiah Biologi, 2019)
Strawberry is fruit commodities which originating from the member of Rosaceae and has been widely cultivated in several countries of the world including Indonesia. One of the strawberry cultivars which consumed and cultivate in Indonesia is the strawberry Festival (Fragaria x ananassa D. var. Festival), which was developed in the area of Banyuroto, Magelang. In order to improve the quality and quantity of strawberry plants, polyploidization using colchicine has been employed in previous studies. The objectives of this research were study the chromosome character which include number, size, shape, and karyotype of normal strawberries and treatment strawberries with colchicine (0.05% 36 hours of root and leaf induction, 0.05% 24 hours of root and leaf induction, 0.05% 36 hours of leaf induction, 0.01% 36 hours of root and leaf induction). The results of this research shown that chromosome number difference and degree of ploidy between Fragaria x ananassa var Chandler in America with Fragaria x ananassa var. Festival in Indonesia due to natural mutation. While Festival strawberry control and treatment colchicine have same number chromosome is 2n=4x=28M and there are a difference long sleeve and short sleeve chromosome that may affect the content of chromosome expression and phenotype character are produced. The analysis of flow cytometry showed that treatment strawberry with colchicine has two peaks with intensity fluorescence equal to strawberry control so that it can be interpreted that the ploidy number of strawberries treatment with colchicine is tetraploid.